The Impact of an Interactive Guidance Intervention on Sustained Social Withdrawal in Preterm Infants in Chile: Randomized Controlled Trial - Bustamante Loyola, Jorge; Pérez Retamal, Marcela; Mendiburo-Seguel, Andrés; Guedeney, Antoine Claude; Salinas González, Ricardo; Muñoz, Lucia; Cox Melane, Horacio; González Mas, José Miguel; Simó Teufel, Sandra; Morgues Nudman, Mónica (Frontiers in Pediatrics, 2022)
Background Sustained social withdrawal is a key indicator of child emotional distress and a risk factor for psychological development. Preterm infants have a higher probability of developing sustained social withdrawal than infants born full-term during their first year. Objective To compare the effect of a behavioral guidance intervention to that of routine pediatric care on sustained social withdrawal behavior in preterm infants. Design Multicenter randomized clinical trial. Participants Ninety nine moderate and late preterm newborns and their parents were recruited and randomized into two groups, i.e., Intervention (n = 49) and Control (n = 50). Both groups attended medical check-ups at 2, 6 and 12 months and were assessed with the Alarm Distress Baby Scale. The intervention group received a standardized behavioral intervention if the neonatologist detected sustained social withdrawal. Also, parents filled out the Edinburgh Postnatal Depression Scale, the modified-Perinatal Posttraumatic Stress Disorder Questionnaire, and the Impact of Event Scale-revised. Results At baseline, the prevalence of withdrawal was 4.0% (95% CI: 0.03–14.2) for the control group and 22.4% (95% CI: 13.0–35.9) for the intervention group [OR = 0.22, p = 0.028 (95% CI =0.06–0.84)]. At 6 months, the prevalence was 10.0% (95% CI: 3.9–21.8) for the control group and 6.1% (95% CI: 2.1–16.5) for the intervention group [OR = 2.09, p = 0.318 (95% CI = 0.49–8.88)]. At 12 months, the prevalence was 22.0% (95% CI: 12.8–35.2) for the control group and 4.1% (95% CI: 1.1–13.7) for the intervention group [OR = 6.63, p = 0.018 (95% CI = 1.39–31.71)]. Logistic generalized estimating equation models were performed. The pooled crude OR (considering diagnosis at 6 and 12 months) was 3.54 [p = 0.022 (95% CI = 1.20–10.44); Cohen's d= 0.70]. In the case of pooled adjusted OR, the model considered diagnosis (0 = Withdrawal, 1 = Normal) as the dependent variable, time of evaluation (1= 6 months, 2 = 12 months) and group (0 = Control, 1 = Experimental) as factors. In this case, the pooled adjusted OR was 3.57 [p = 0.022 (95% CI = 1.20–10.65); Cohen's d = 0.70]. Conclusion Assessment and intervention of sustained social withdrawal in preterm infants via standardized instruments benefits families by reducing its prevalence, and possible associated negative outcomes. Clinical Trial Registration ClinicalTrials.gov; https://clinicaltrials.gov/ct2/show/NCT03212547, identifier: NCT03212547.